Teaching the Bible and Popular Media as Part of Contemporary Rape Culture - Lawrence, Beatrice J. W. (The Oxford handbook of feminist approaches to the Hebrew Bible, 2020)
This essay explores pedagogical strategies for addressing rape culture in biblical studies courses, employing Genesis 34 and Judges 19–21 as primary texts. The first section discusses the nature of popular culture and its impact on gender. The following four sections highlight cultural myths about sexual assault by focusing on significant biblical texts and incorporating aspects of popular media to facilitate conversations about rape culture. The conclusion summarizes the main points and encourage further studies that combine the study of popular media and biblical texts. Overall, the essay contributes to the reading and teaching of the Bible within contemporary rape culture so that students become critical interpreters of biblical texts, as they become resistant readers of past and present rape culture.